Investigating the Expertise Indicators of Vulnerability Discovery Professionals - Mortada Al-Banna; Boualem Benatallah; Moshe Chai Barukh (Advances in Science, Technology and Engineering Systems Journal, 2017)
In crowdsourcing, selecting the person with suitable expertise is very important; especially since the task requester is not always in direct contact with the worker. Recently, this has become increasingly important particularly when the crowdsourced tasks are complex and require skillful workers (e.g. software development, software testing, vulnerability discovery, and open innovation). In this paper, we investigate the expertise indicators of vulnerability discovery professionals in a crowdsourcing vulnerability discovery platform. We conduct a systematic literature review, we review online contents, conduct interviews with domain experts, and survey vulnerability discovery professionals involved in the task of vulnerability discovery. We discuss the indicators we have found, and we provide some recommendations to help improve the process of selecting vulnerability discovery professionals to perform crowd tasks related to vulnerability discovery.
Keywords: Crowdsourcing; Expertise; Vulnerability Discovery Professionals